1983
DOI: 10.1017/s0022112083002657
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the electrohydrodynamic flow in electrostatic precipitators

Abstract: Schlieren visualization and laser-anemometry experiments are presented which demonstrate that a two-dimensional positive corona discharge interacts with the flow of a wire–plate electrostatic precipitator to produce a non-turbulent secondary flow in a plane perpendicular to the discharge wires. Smoke-wire visualization and hot-wire anemometry experiments are then described which show that negative-corona-discharge non-uniformities are responsible for producing both secondary flow in a plane parallel to the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 5 publications
7
47
0
2
Order By: Relevance
“…It has been observed that the distance between spikes is critical for the flow pattern: for larger distances a well-organized spiral flow is formed, while at the reduced distance a turbulent flow arises. These agreed with the earlier experimental observations: for the positive corona discharge, which is uniform along the corona wire, the flow turbulence increases only slightly whereas the negative corona discharge strongly reinforces the turbulence intensity [8,9]. …”
Section: Introductionsupporting
confidence: 93%
“…It has been observed that the distance between spikes is critical for the flow pattern: for larger distances a well-organized spiral flow is formed, while at the reduced distance a turbulent flow arises. These agreed with the earlier experimental observations: for the positive corona discharge, which is uniform along the corona wire, the flow turbulence increases only slightly whereas the negative corona discharge strongly reinforces the turbulence intensity [8,9]. …”
Section: Introductionsupporting
confidence: 93%
“…This pattern qualitatively supported the findings of past numerical investigations by Lei et al [18] and Zhao [19]. Such a phenomenon has also been observed by Leonard [20]. However, the formation of this EHD pattern has not been explained so far and few of the recent visualization studies with solid particles provided in the introduction part mentioned the existence of this flow pattern.…”
Section: B Ehd Flow Transitionsupporting
confidence: 90%
“…Since Leonard et al (1983) and Yamamoto (1989) emphasize the importance of controlling the quality of flow characteristics, an internal diameter D, of 650 mm was chosen as a compromise between the flow regime, which should be laminar to maximize the capture efficiency, and the flow rate, that should be as high as possible. The radius was subsequently defined by choosing a Reynolds number slightly lower than 2000 for the flow rate of 100 L/min.…”
Section: Air Sampler Design and Performancementioning
confidence: 99%